DOMESTIC OUTCOMES OF NIGERIA'S ECONOMIC DIPLOMACY 1999-2007 (2014)
Economic Diplomacy(ED) is the management of international relations aimed at promoting exports and increasing access to Foreign Direct Investment (FDI). Nigeria has embarked on various policy reforms including bank recapitalization policy, privatization, anti-corruption campaign, and poverty alleviation. However, various studies on Nigeria's ED had focused more on the process of its implementation rather than its outcomes. This study, therefore, investigated the outcomes of the various ED policies on the nation's Gross Domestic Product (GDP); FDI, citizens' ability to meet family obligations and democratic participation. The political-economy theory was employed. A Cross-sectional survey research design, was conducted using a semi-structured questionnaire elicited information on citizens' perception of the outcomes of ED on democratic participation and ability to meet family obligations. Convenience sampling technique was used to select a total of 1029 respondents, comprising of 509 from the Northand 520 from the South. Eight In-depth Interviews(IDIs) were conducted with selected members of Senate Committees on Foreign Affairs, Privatisation, and Banking; Director of Research and a research fellow of the Nigeria Institute of International Affairs; an anthropology scholar and two research officers of Non-governmental Organisations. Publications of Central Bank of Nigeria, Africa Peer Review Mechanism country report and press reports were used to obtain data on the outcomes of ED policies on the nation's GDP and inflow of FDI. While secondary data was content analysed, primary data was analysed using descriptive statistics. The ED policies increased international trade and resulted in increases in the nation's GDP and FDI inflows by 5.5% and 61.9%, respectively. However, bank recapitalization policy and privatisation caused loss of jobs. Poverty alleviation enhanced self-employment and improved democratic participation. Improvement in citizen's democratic participation following poverty alleviation and privatization programmes, was indicated by more respondents in the North (18.8% and 11.9%respectively) than in the South (10% and 10.7% respectively). Conversely, increases in citizens' democratic participation, due to recapitalisation policy and anti-corruption reforms were reported bymore respondents in the South (35% and 15.7% respectively) than in the North (20.8%and 16.0% respectively). Privatization and bank recapitalisation policy was also indicated withability to meet family obligationsby more respondents in the South (15.7% and 20.8% respectively) than the North (12.3% and 20.2% respectively). Also more respondents in the South (19.5%) than the North (16.1%) reported that ability to meet family obligations was due to poverty alleviation programme. However, only 11.5% from North and 11.3% from South reported that bank recapitalisation policy enhancedability to meet family obligations. In addition, IDIs revealed that ED generally improved the nation's GDP and FDI but did not improve the social well-being and democratic participation. Nigeria's economic diplomacy contributed positively to increased Gross Domestic Product and inflow of Foreign Direct Investments. However, it led to job losses and did not improve citizens' ability to meet basic family needs and democratic participation. Policy makers should implement policies, that could improve the well-being of the citizens.